Albania : Report on Observance of Standards and Codes-Fiscal Transparency. (IMF Staff Country Reports; Country Report, 2003)
Albania has made much progress in recent years in improving fiscal transparency and meets the standards of the fiscal transparency code in several areas. However, shortcomings exist in the transparency of tax laws and instructions, and in budget preparation and the quality of budget documents. The appropriation structure in the budget document should be expanded as soon as possible. Transparency of tax legislation should be implemented. The government should develop formal guidelines and procedures for evaluating and prioritizing projects included in the investment budget.